The α-Subunit of the Arabidopsis Heterotrimeric G Protein, GPA1, Is a Regulator of Transpiration Efficiency(1)([C])([W])([OA]) - Nilson, Sarah E. (American Society of Plant Biologists, 2010)
Land plants must balance CO(2) assimilation with transpiration in order to minimize drought stress and maximize their reproductive success. The ratio of assimilation to transpiration is called transpiration efficiency (TE). TE is under genetic control, although only one specific gene, ERECTA, has been shown to regulate TE. We have found that the α-subunit of the heterotrimeric G protein in Arabidopsis (Arabidopsis thaliana), GPA1, is a regulator of TE. gpa1 mutants, despite having guard cells that are hyposensitive to abscisic acid-induced inhibition of stomatal opening, have increased TE under ample water and drought stress conditions and when treated with exogenous abscisic acid. Leaf-level gas-exchange analysis shows that gpa1 mutants have wild-type assimilation versus internal CO(2) concentration responses but exhibit reduced stomatal conductance compared with ecotype Columbia at ambient and below-ambient internal CO(2) concentrations. The increased TE and reduced whole leaf stomatal conductance of gpa1 can be primarily attributed to stomatal density, which is reduced in gpa1 mutants. GPA1 regulates stomatal density via the control of epidermal cell size and stomata formation. GPA1 promoter::β-glucuronidase lines indicate that the GPA1 promoter is active in the stomatal cell lineage, further supporting a function for GPA1 in stomatal development in true leaves.